2022
DOI: 10.1167/iovs.63.5.35
|View full text |Cite|
|
Sign up to set email alerts
|

Cortical Atrophy Predicts Visual Performance in Long-Term Central Retinal Disease; GCL, pRNFL and Cortical Thickness Are Key Biomarkers

Abstract: Purpose The aim of this study was to assess both retinal and cortical structure in a cohort of patients with long-term acquired central retinal disease in order to identify potential disease biomarkers and to explore the relationship between the anterior and posterior visual pathways. Methods Fourteen participants diagnosed with long-term central retinal disease underwent structural assessments of the retina using spectral-domain optical coherence tomography, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…These results support and extend previous cross-sectional studies, which have highlighted reductions associated with natural ageing, and also largely supports previous work reporting a thinning of cortex in the posterior visual pathway in MD 1 , 3 , 5 , 8 , 10 , 12 , 16 , 17 . The group data for cortical thickness support earlier work in our lab; Hanson et al 17 followed a group of unilateral AMD patients and found a reduction in volume of the occipital lobe, driven by cortical thinning in the occipital pole.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results support and extend previous cross-sectional studies, which have highlighted reductions associated with natural ageing, and also largely supports previous work reporting a thinning of cortex in the posterior visual pathway in MD 1 , 3 , 5 , 8 , 10 , 12 , 16 , 17 . The group data for cortical thickness support earlier work in our lab; Hanson et al 17 followed a group of unilateral AMD patients and found a reduction in volume of the occipital lobe, driven by cortical thinning in the occipital pole.…”
Section: Discussionsupporting
confidence: 92%
“…The group data for cortical thickness support earlier work in our lab; Hanson et al 17 followed a group of unilateral AMD patients and found a reduction in volume of the occipital lobe, driven by cortical thinning in the occipital pole. Furthermore, in a separate cohort of bilateral wet-AMD patients, Hanson et al 16 found the occipital pole and calcarine sulcus both showed significant thinning. Here, we report cortical thinning in the same ROIs in a different cohort of bilateral MD patients.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations